(untitled) (Bioagro, 2026)
The physicochemical characterization constitutes a strategic input for tomato selection and improvement programs aimed at the conservation and use of local phytogenetic resources, as well as the diversification of horticultural products adapted to the agroclimatic conditions of the country. This study presents the results of the characterization of fruits from 18 wild and cultivated tomato (Solanum spp.) accessions collected in different agroecological regions of Venezuela and grown in a greenhouse for characterization within the framework of the Tomato Germplasm Development Project, carried out by the National Center for Agricultural Research (CENIAP) of the National Institute for Agricultural Research (INIA). Standardized protocols were used to measure physical variables (weight, size, shape, number of locules, firmness, and juice yield) and chemical variables (total soluble solids content, titratable acidity, pH, and total carotenoid content). The analysis of variance and comparisons of means indicated highly significant differences among the accessions for most of the variables studied, which is evidence of a wide genetic variability among the materials evaluated. Principal component analysis (PCA) reduced the dimensionality of the data, explaining 46.6 % of the total variance in the first component (CP1) and 15.1 % in the second (CP2). Cluster analysis also revealed the formation of four distinct groups, whose means showed significant differences in several physicochemical variables. These results made it possible to identify accessions with desirable characteristics such as fresh consumption, processing or genetic improvement.